Examining the interplay of information, emotions, and behavior: PLS-ANN analysis - Gary, Joston (Frontiers in Communication, 2024)
The study investigates how platform information push sways emotions to influence online purchase outcomes in Macau e-commerce. Employing PLS-ANN analysis of survey data from 871 platform users, results revealed push enhances pleasure but mitigates annoyance. In turn, pleasure elevates while annoyance reduces purchase intention and behavior. Interestingly, accuracy exhibited no direct impact but moderated annoyance when interacting with push. Findings provide novel empirical evidence on push mechanisms and actionable strategies for optimizing emotive resonance. Key contributions include elucidating emotions' mediating role, expanding affect-as-information theory and emotional contagion theory, and offering statistically significant recommendations to maximize Macau online sales through information-emotion synergy. Additional dimensions like crossareas, experimental, neural and cross-platform comparisons would enrich this affective research avenue as digital buying gains dominance. Effectively leveraging emotive motivators through impactful, irritation-reducing pushes may hold the key to purchase maximization.